In silico Analysis, Molecular Docking, Molecular Dynamic, Cloning, Expression and Purification of Chimeric Protein in Colorectal Cancer Treatment - Dana H; Mahmoodi Chalbatani G; Gharagouzloo E; Miri SR; Memari F; Rasoolzadeh R; Zinatizadeh MR; Kheirandish Zarandi P; Marmari V (Dove Medical Press, 2020)
Hassan Dana, 1, 2,* Ghanbar Mahmoodi Chalbatani, 1,* Elahe Gharagouzloo, 1 Seyed Rouhollah Miri, 1 Fereidoon Memari, 1 Reza Rasoolzadeh, 3 Mohammad Reza Zinatizadeh, 3 Peyman Kheirandish Zarandi, 3 Vahid Marmari 2 1Cancer Research Center, Cancer Institute of Iran, Tehran University of Medical Science, Tehran, Iran; 2Department of Biology, Damghan Branch, Islamic Azad University, Damghan, Iran; 3Department of Biology, Science and Research Branch, Islamic Azad University, Tehran, Iran*These authors contributed equally to this workCorrespondence: Fereidoon Memari; Sayed Rohollah MiriCancer Research Center, Cancer Institute of Iran, Tehran University of Medical Science, Tehran, IranTel +98-910-5040-602; +98-912-6543-321Email memarife@tums.ac.ir; Srmiri@sina.tums.ac.irIntroduction: Colorectal cancer (CRC) is a type of cancer in humans that leads to high mortality and morbidity. CD166 and CD326 are immunoglobulins that are associated with cell migration. These molecules are included in tumorigenesis of CRC and serve a great marker of CRC stem cells. In the present study, we devised a novel chimeric protein including the V 1-domain of the CD166 and two epitopes of CD326 to use in diagnostic or therapeutic applications.Methods: In silico techniques were launched to characterize the properties and structure of the protein. We have predicted physicochemical properties, structures, stability, MHC class I binding properties and ligand-receptor interaction of this chimeric protein by means of computational bioinformatics tools and servers. The sequence of chimeric gene was optimized for expression in prokaryotic host using online tools and cloned into pET-28a plasmid. The recombinant pET28a was transformed into the E. coli BL21DE3. Expression of recombinant protein was examined by SDS-PAGE and Western blotting.Results: The designed chimeric protein retained high stability and the same immunogenicity as of the original proteins. Bioinformatics data indicated that the epitopes of the synthetic chimeric protein might induce B-cell- and T-cell-mediated immune responses. Furthermore, a gene was synthesized using the codon bias of a prokaryotic expression system. This synthetic gene expressed a bacterial expression system. The recombinant protein with molecular weights of 27kDa was expressed and confirmed by anti-his Western blot analysis.Conclusion: The designed recombinant protein may be useful as a CRC diagnostic tool and for developing a protective vaccine against CRC.Keywords: chimeric protein, molecular docking, molecular dynamic, vaccine